Four new monoterpenoids from the whole plants of Valeriana stenoptera. Issue 9 (2nd September 2019) - Dong, Fa-Wu; Yang, Liu; Zi, Chen-Ting; Li, Bao-Jing; Li, Hui-Yuan; Li, Wen-Jie; Yang, Yu-Lin; Hu, Jiang-Miao; He, Hong-Ping
Abstract: Four new monoterpenoids, including two new acyclic monoterpenoids (2 R, 6 R )-2, 6-dimethyl-8-isovaleroxyoctan-1-ol (1 ) and (2 S, 6 S )-2, 6-dimethyl-8-isovaleroxyoctan-1-ol (2 ), as well as two new iridoids stenopterins F-G (3 and4 ), together with fifteen known compounds (5–19 ), were isolated from whole dried material of Valeriana stenoptera . Stenopterin F was the first reported iridoids with n -butoxyl in the Valerianaceae family. The structures of new compounds were established on the basis of extensive spectroscopic analysis.